2016
DOI: 10.2196/resprot.5747
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness Of Social Media (Facebook) Compared With More Traditional Advertising Methods for Recruiting Eligible Participants To Health Research Studies: A Randomized, Controlled Clinical Trial

Abstract: BackgroundRecruiting participants for research studies can be difficult and costly. The popularity of social media platforms (eg, Facebook) has seen corresponding growth in the number of researchers turning to social networking sites and their embedded advertising frameworks to locate eligible participants for studies. Compared with traditional recruitment strategies such as print media, social media advertising has been shown to be favorable in terms of its reach (especially with hard-to-reach populations), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
143
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(157 citation statements)
references
References 23 publications
13
143
1
Order By: Relevance
“…The percentage of participants recruited via social media ranged from 0% (0/12) to 98.29% (1610/1638) [14-42] as shown in Table 1, and the median percentage was 32%. The article by Head et al [35] has 2 studies and has been counted as 2 articles for the purpose of Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of participants recruited via social media ranged from 0% (0/12) to 98.29% (1610/1638) [14-42] as shown in Table 1, and the median percentage was 32%. The article by Head et al [35] has 2 studies and has been counted as 2 articles for the purpose of Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In further sections of this paper, the article by Head et al [35] is counted as a single article or 2 articles, according to whether the conclusions from the 2 studies pertinent to the outcomes of this paper are the same or different. Out of 30 studies, 12 studies (40%) reported higher rates of recruitment through social media as compared with any of the other methods used [14-17,26,28,31,32,35, 36,41,42] and 15 studies (50%) reported recruitment via social media to be less effective than at least one other method used [18-21,23-25, 27,33-35,37-40]. Heffner et al [20] and Rabin et al [24] found social media to be the least effective method out of multiple (>2) recruitment methods used.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, print advertisements, such as newspaper and magazine ads, have become a primary option for many research studies 13 . This is an excellent strategy to reach a broader population, and have shown promising results for diseases that have a high prevalence.…”
Section: Strategy 1: Newspaper and Magazine Adsmentioning
confidence: 99%
“…It is only when the study generates topics of “human interest” that social media is effective; therefore a mass campaign of online dissemination could be effective for enrollment only when captivating and media-appropriated materials are created in regards of the research topic. However, in order to achieve efficient results, it requires a large dedication of time by the research staff 13,28 .…”
Section: Strategy 4: Developing a Blog/websitementioning
confidence: 99%
“…Thornton and colleagues [6] reviewed 110 unique studies that used Facebook to recruit participants for health, medical, or psychosocial research and found that the participants were generally similar to those recruited via traditional methods. Frandsen, Thow, and Ferguson [7] showed that participants recruited to their smoking cessation study via social as compared to traditional media were somewhat younger (mean age 39.3 years vs. 44.9 years) but otherwise demographically similar (gender, education, and income). Those recruited via traditional media were more likely to follow the study protocol and "complete" the study.…”
Section: Recruitment Strategies For Ehealth Studiesmentioning
confidence: 99%